Relationship of Stuttering to Word Information Value in a Phonemic Clause - Jayaram M (Journal of All India Institute of Speech and Hearing, 1970)
There have been a number of studies which have demonstrated a relation between word position in a sentence and stuttering (Brown, 1938; 1945; Hejna, 1955; Quarrington, 1956; Quarrington, Conway and Siegel, 1962). In general, these studies have reported a higher stuttering on the initial words of a sentence than on the subsequent words. Blankenship (1964) found this to be true of non-stutterers and Bloodstein and Gantewerk (1967) of young stutterers, Taylor (1966) showed that word position was a more important determiner of the loci of stuttering instances than either word length or the phonetic factors.